The Relationship between Social Media Exposure to MBG Food Safety News and Risk Perception and Trust among Active Users in Blitar - Nur Agustin Mardiana; Dea Melani; Wylla Septa Ayu; Octo Riko Jauhar Ramadhani (Universitas Islam Raden Rahmat, Malang, 2026)
The proliferation of food safety narratives on social media platforms has raised concerns about their influence on public perception and acceptance of government nutritional programs. This study examines the relationships between social media exposure to food safety news related to the Free Nutritious Meal Program (Makan Bergizi Gratis/MBG), information source credibility, food safety risk perception, and public trust and acceptance among active social media users in Blitar, Indonesia. A quantitative descriptive-correlational design was employed, involving 109 purposively sampled respondents who met the inclusion criteria of active social media use and prior exposure to MBG-related content. The findings reveal that both social media exposure and information source credibility significantly predicted risk perception, while information source credibility emerged as the dominant predictor of public trust and acceptance (R² = 33.41%). In contrast, risk perception did not significantly predict trust and acceptance (α = -0.043; p = 0.658), nor did social media exposure directly influence trust (p = 0.836), leaving the hypothesised mediating role of risk perception unsupported. These findings underscore that building a credible and trustworthy information ecosystem is more effective than merely increasing positive content volume in sustaining public trust in the MBG program.